Pengaruh Pembelajaran Daring di Masa Covid 19 terhadap Motivasi Belajar Siswa Kelas X SMK TIK-MM Swasta Rakyat Sei Glugur - Ginting, Rahmadani Fitri; Lubis, Harun; Ciptasari Br Ginting; Tirta Yogi Aulia (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
Online learning is an electronic learning system, using electronic media, internet, computer, gedget (HP), and multimedia files (sound, pictures and video). Learning motivation is the overall driving force in the student that moves the student and gives rise to the learning activity so that the desired goal of the learning subject can be achieved. This research is quantitative research that examines phenomena objectively by using statistical calculations to test hypotheses in research. The sample of this study amounted to 30 people with total sampling technique. The test result of product moment r value is positive 0.632 and perolehan p count = 0.000 < 0.05 which indicates that online learning variables (variable X) and learning motivation variable (variable Y) have a significant influence. Anova regression analysis test obtained an F value of 18,628 and a sig value. That is 0.000 < 0.05, so it can be concluded that Ha was accepted and Ho rejected. The result of the determinant coefficient, known determinant cofisien value of 0.399 which means variable X (Online Learning) affects variable Y (Learning Motivation) by 39.9%.